Genetic diversity of native Bradyrhizobium populations in soybean-growing areas of northern Thailand - Shutsrirung A. (2014)
Native Bradyrhizobium isolates (66 isolates) obtained from traditional soybean-growing areas of northern Thailand were classified using 3 genotypic methods: repetitive extragenic palindromic (REP) sequences, enterobacterial repetitive intergenic consensus (ERIC) sequences together with the polymerase chain reaction (PCR) and mapped restriction site polymorphism (MRSP) analysis of 16S rRNA genes. Sequencing of the 16S rRNA genes was performed for some isolates representing the major REP-ERIC-PCR clusters to acquire data supporting the classifications. The results of the classifications using all these genotypic methods appeared to be consistent, with some minor differences. Five major clusters were obtained by integration of all the classifications: clusters Bj-A (B. japonicum), Bj-B, Brh1, Brh2, and Be (B. elkanii). Two clusters, Brh1 and Brh2 were distantly related to B. japonicum USDA110 and B. japonicum strains, but were genetically close to B. liaoningense. Cluster Bj-B was closer to USDA110 than the Brh-clusters but the phylogenetic positions were clearly separated from each other. The cowpea Bradyrhizobium isolates capable of nodulating soybean were distributed and classified into all of these five clusters. The results revealed unique genetic characters of the Thai soybean-bradyrhizobia. The classification of these native bradyrhizobia using REP and ERIC-PCR as well as the serotype pattern of these isolates reflected well the phylogenetic relationships among isolates based on differences in 16S rDNA sequences. Our results also indicated the existence of a relationship between the genotype of the native isolates and sampling locations. Some genotypic-clusters; Brh1, Brh2, and Bj-A were mainly obtained from Chiang Mai Province and a certain cluster, Bj-B from Mae Hong Son Province. This relationship was not observed for cluster Be. In contrast to the sampling locations, no relationship was detected between host cultivars and genotype recovery.